Non-traumatic myositis ossificans mimicking a malignant neoplasm in an 83-year-old woman: a case report - Nishio, Jun (BioMed Central, 2010)
INTRODUCTION: Myositis ossificans is a benign, self-limiting condition that usually affects young, athletically active men. To the best of our knowledge, this case report describes the oldest recorded patient with myositis ossificans. CASE PRESENTATION: Our patient was an 83-year-old Japanese woman who presented with a one week history of a palpable mass in the left thigh. She had a history of surgery for transverse colon cancer and lung cancer at the ages of 73 and 80, respectively. Clinical and radiological examinations suggested a malignant neoplasm such as metastatic carcinoma or extraskeletal osteosarcoma. A diagnosis of myositis ossificans was made by core needle biopsy. Our patient was asymptomatic and had no recurrence at one year follow-up. CONCLUSION: Clinicians should consider myositis ossificans as a possible diagnosis for a soft tissue mass in the limb of an older patient, thereby avoiding unnecessarily aggressive therapy.